Study on The Development of Chains of Producers in The Food Industry In Brăila County, Romania - Violeta GAGU (LEOCĂ); Gheorghe Adrian ZUGRAVU (Communications of International Proceedings, 2022)
Economic activity is characterized by the existence of two essential functions: consumption and production. However, their analysis cannot be done in general but by individualizing some elements. By its nature, man cannot exist as an individual and as a species without consuming. Consumption varies greatly from individual to individual, from country to country and from one era to another. Also, consumption varies depending on the resources that man has, be they material or spiritual. The demand from the food industry in Brăila County, Romania is provided by the income obtained in the supply (production) sphere. It follows that the market can self-regulate
Keywords: Food Chain; Producers; Consumption.